Load-Carrying Capacity of Thin-Walled Composite Columns with Rectangular Cross-Section under Axial Compression - Rozylo, Patryk; Rogala, Michal; Pasnik, Jakub (Materials, 2024)
The aim of the current study was to determine the load capacity of composite columns subjected to axial compressive load. The subjects of the study were two types of columns with a rectangular cross-section, with different edge lengths. The tested columns had a closed cross-section. Four different fiber arrangements were analyzed for both cross-sections studied. The research was realized using interdisciplinary methods to determine the mechanism of damage to the composite material, with particular emphasis on damage initiation and propagation. Experimental tests were realized on a testing machine, the analysis was carried out with an acoustic emission system, and image analysis using visual assessment system of deflections of the walls of the structure. In addition, a number of numerical analyses were realized based on advanced modeling techniques for fiber-reinforced composites. A comparative analysis of both quantitative and qualitative results is presented for both analyses. The innovation of the presented research lies in the development of a custom method for modeling structures made of composite material with special emphasis on the failure phase. This will allow to accurately reflect the modeling of thin-walled structures with closed cross-section subjected to loading in a complex stress state.